Dens evaginatus and dens invaginatus: A report of two cases - Hegde Shruthi; Shanti Kamath Jasmine; Ajila Vidya; Babu Subhas; Bhat Supriya (Medicinski fakultet i Klinika za stomatologiju, Niš, 2020)
Introduction: Developmental disturbances of teeth at the stage of morpho-differentiation have been related to abnormalities associated with changes in the tooth shape and size. Dens evaginatus and dens invaginatus are the developmental variations of the human dentition. Dens evaginatus, a rare anomaly characterized by the presence of a tubercle on the occlusal surface of teeth is seen to occur due to abnormal proliferation and folding of the inner enamel epithelium and part of the dental papilla into the stellate reticulum of the enamel organ; whereas, dens invaginatus is seen to occur due to infolding of the enamel and dentine into the pulp cavity and sometimes extending to the root apex. Case report: We report cases with bilateral dens evaginatus in mandibular second premolars and dens invaginatus in maxillary lateral incisor. Conclusion: Such developmental anomalies of teeth deserve clinical importance, as high chances of early pulpal pathosis.